(untitled) (Journal of Medical & Health Sciences Review, 2025)
Phytofabricated nanoparticles represent a groundbreaking advancement in green nanotechnology, offering a safe and eco-friendly alternative to conventional synthesis methods. This study explores the mechanisms and biomedical potential of plant-derived nanoparticles, focusing on their synthesis, characterization, and therapeutic applications. Using Azadirachta indica (neem) leaf extract, we successfully synthesized silver (AgNPs) and zinc oxide (ZnO NPs) nanoparticles under optimized conditions (pH 10, 60°C, 1 mM precursor concentration). Characterization via UV-Vis spectroscopy, FTIR, XRD, SEM, and DLS confirmed the formation of spherical, crystalline nanoparticles (ZnO NPs: 65.09 nm, PdI 0.740; zeta potential: -26.1 mV) with phytochemical capping, as evidenced by FTIR peaks at 3233 cm⁻¹ (O-H) and 1640 cm⁻¹ (C=O). The nanoparticles exhibited significant biomedical potential: (1) Antioxidant activity (IC₅₀ = 0.74 mg/mL for ZnO NPs in DPPH assay); (2) Dose-dependent cytotoxicity against MCF-7 breast cancer cells, suggesting ROS-mediated apoptosis; (3) Broad-spectrum antimicrobial effects against Staphylococcus aureus, Escherichia coli, and Klebsiella pneumoniae; and (4) Selective toxicity (lower viability in MCF-7 vs. RAW264.7 macrophages), highlighting cancer-targeting potential. These findings underscore the dual advantage of phytofabricated nanoparticles—combining therapeutic efficacy with environmental sustainability. Their green synthesis aligns with UN Sustainable Development Goals (SDG 3, 9, 12), while their multifunctionality (antioxidant, anticancer, antimicrobial) positions them as promising candidates for drug delivery, wound healing, and precision oncology. Future research should address scalability, long-term biosafety, and clinical translation to harness their full potential in nanomedicine.